Cadaveric Analysis of the Distal Tibiofibular Syndesmosis. (August 2016) - Lilyquist, Michael; Shaw, Adam; Latz, Kevin; Bogener, James; Wentz, Brock
Background: Unstable ankle fractures with syndesmotic injuries commonly occur and can result in significant morbidity. Although the need for an anatomic reduction is clear, there is still debate surrounding the optimal operative treatment. Recent literature shows an increasing interest in anatomic ligament repair or reconstruction in the acute and chronic syndesmosis injury. Despite this trend, there is insufficient literature detailing anatomy of the distal tibiofibular syndesmosis. In the literature that does exist, there is controversy regarding the ligamentous anatomy of the syndesmosis. None of the current literature describes an anatomic constant that may be used as an intraoperative reference for anatomic ligament reconstructions. Methods: Ten sets of tibia and fibula free of all soft tissue were used to analyze osseous structures. Another 10 nonpaired, fresh-frozen specimens were used to study the distal tibiofibular syndesmosis. These were measured using a 3-dimensional tracking system. Measurement of each ligament width at origin and insertion, length, and distance from the tibial articular cartilage was performed. Results: The superior and inferior insertions of the anterior inferior tibiofibular ligament measured 22.7 mm and 3.4 mm proximal to the distal articular cartilage of the tibia, respectively. The superior insertion of the posterior inferior tibiofibular ligament measured 15.2 mm proximal to the articular cartilage. The superior and inferior insertions of the interosseous ligament measured 31.8 mm and 9.2 mm proximal to the distal articular cartilage, respectively. The inferior transverse ligament was a prominent identifiable structure in 70% of specimens. Conclusions: The superior margin of the distal articular cartilage could serve as a consistent anatomic landmark for reconstruction. The inferior transverse ligament is an identifiable structure in 70% of the specimens studied. Clinical Relevance: This article clarifies the anatomy and provides measurements from an anatomic constant that can guide reconstruction and intraoperative evaluation of the syndesmosis.